2003
DOI: 10.1016/s1044-0305(03)00141-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of selenium from selenoproteins: Conversion of selenocysteine to dehydroalanine in vitro

Abstract: Characterization of reduced and alkylated rat selenoprotein P by mass spectrometry yielded selenopeptides from which one or more selenium atoms were missing. Predicted selenopeptide mass peaks were accompanied by peaks corresponding to the conversion of one or more selenocysteine residues to dehydroalanine(s). Experiments were carried out to determine whether this loss of selenium occurred in vitro. A selenopeptide was isolated that contained two selenocysteine residues that were both in selenide-sulfide linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…However, DHA is not frequently found in positions corresponding to Cys residues. This difference is likely attributable to the greater strength of the C-S bond (272 kJ=mol) compared with that of the C-Se bond (234 kJ=mol) (25). These multiple sources of DHA are consistent with our observation that direct blot analysis of crude RBC extracts yielded many positive bands (not shown).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, DHA is not frequently found in positions corresponding to Cys residues. This difference is likely attributable to the greater strength of the C-S bond (272 kJ=mol) compared with that of the C-Se bond (234 kJ=mol) (25). These multiple sources of DHA are consistent with our observation that direct blot analysis of crude RBC extracts yielded many positive bands (not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Tryptic peptides prepared from selenoproteins have previously been observed to have lost Sec residues as a result of their conversion to DHA during protein purification or digestion (25,30). To determine whether GPx1 might lose selenium under oxidative stress, we incubated human GPx1 with 1 mM H 2 O 2 for 1 h at 378C.…”
Section: Conversion Of Sec To Dha In Gpx1 Treated With H 2 Omentioning
confidence: 99%
“…An in depth investigation of the Se-incorporation in protein by 2D GE -LA-ICPMS, demonstrated that in this L. reuteri strain all the Se present in the proteins is incorporated as selenocysteine (SeCys), whereas methionine/selenomethionine substitution, which is typical for other microorganisms, such as yeast (25), did not occur. Note also that, in contrast to literature (26), the method developed here allows the preservation of the SeCys moiety during analysis Indeed, no dehydroalanine residues were detected.…”
Section: Discussionmentioning
confidence: 79%
“…Ma et al (30) observed the conversion of one or more selenocysteine residues of rat selenoprotein P to dehydroalanine, probably through the mechanism of oxidation of selenocysteine followed by a syn-␤-elimination of selenenic acid. The calculated mass of a PrxU variant containing dehydroalanine instead of selenocysteine would be 23,555 Da.…”
Section: Discussionmentioning
confidence: 99%